Invited commentary: Invited commentary on … Lithium treatment and risk for dementia in adults with bipolar disorder†. (July 2015) - Sutherland, Calum; Duthie, Ashleigh C.
Summary: Alzheimer's disease clinical trials are failing at an alarming rate, highlighting the desperate need for novel thinking to combat this escalating health crisis. A recent large-scale population study indicates that lithium treatment reduces dementia development, supporting preclinical mechanistic evidence that this commonly used agent might be clinically valuable in dementia.